Od tradycji ludowej do nowoczesnej tożsamości. Wernakularne krajobrazy w poezji Bruna Casilego - Janion, Ewa Róża (Przestrzenie Teorii, 2025)
This paper discusses attitudes towards the southern Calabrian landscape as described in Bruno Casile’s poetry collection Strafonghia sto Skotidi (A Light in the Darkness, 1991). It demonstrates that the experience of the landscape, related to the lives of shepherds and farmers and expressed in the vernacular, oral Greek-Calabrian language, is rooted in the tradition of folk songs and distinct from the approach of the elites (Edward Lear, Antonio Marzano). It is argued that Casile seeks in the multigenerational engagement with the landscape a source of Greek-Calabrian identity, combining class consciousness and a narrative of the linguistic minority’s shared origin. The interpretations of Casile’s poetry contribute to discussions about the meanings of vernacular (social, participatory) landscapes and the class dimension of aesthetic landscape experience.